Validation of an instrument to measure perceptions of digital competences in teachers - Velázquez Cortés, Suhail; Veytia Bucheli, María Guadalupe (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The purpose of this study is to validate an instrument of the attitudes of the teacher of the disciplinary academies of the first semester of the upper secondary level regarding the use of ICT in their teaching practice within the framework of the new educational normality, focusing on the referential context of the number one preparatory school belonging to the Autonomous University of the State of Hidalgo (UAEH), an institutional body with a public and autonomous character. To carry out this research, the indicators associated with the attitudinal dimension regarding the use of ICT were selected: positive, open and critical attitude, empathy, perception of self-knowledge, resilience and/or adaptation to change.